Does the Integrated Discovery Learning STEM Model Improve Students' Problem Solving Skills in Chemistry Learning? Meta-Analysis Study - Erni Johan; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
The industrial revolution 4.0 has a significant impact on chemistry learning. Learning chemistry leads students to have problem-solving thinking skills in learning. There are many studies on STEM-integrated discovery learning models, but no overall effect size has been found from previous studies. This study aims to determine the effect of the size of the STEM-integrated discovery learning model on students' problem-solving skills. This type of research is quantitative research with a meta-analysis approach. The samples came from analyses of national and international journals. Inclusion criteria are publications derived from journals or proceedings indexed by SINTA and Scopus, experimental or quasi-experimental method research, research published in 2021-2024, research must be relevant, data search through google scholar, Springer, Hindawi, ScienceDirect and ERIC databases and Researchgate, research must have complete data to calculate effect size, and a sample size of ≥ 20 students. data analysis through JASP application. The results of the study concluded from the analysis of 19 heterogeneous and normally distributed journals explained the significant effect of the STEM-integrated discovery learning model on students' problem-solving skills (p < 0.001; rRE = 0.940) with high criteria